2022
DOI: 10.1001/jamanetworkopen.2022.10180
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Antimicrobial Stewardship in a High–Antibiotic Resistance Setting

Abstract: Key Points Question Can the outcomes associated with an antimicrobial stewardship program be sustained in the long term? Findings In this cohort study, after implementation of prospective review and feedback, the use trends increased for piperacillin-tazobactam and carbapenems and declined for other broad-spectrum antibiotics. After the addition of a computerized decision support system, the use trends decreased for piperacillin-tazobactam and carbapenems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…9 Another recent study from Singapore found that an intensive antimicrobial stewardship program employing prospective review and computerized decision support systems was associated with limiting the use of pipercillin-tazobactam and carbapenems while reducing use of other antibiotics as well. 10 Our findings suggest opportunities for further de-escalation that can occur based on quantitative assessments of antibiotic spectrum, especially for patients with bacteria-culture-negative HAP and VAP.…”
Section: Discussionmentioning
confidence: 75%
“…9 Another recent study from Singapore found that an intensive antimicrobial stewardship program employing prospective review and computerized decision support systems was associated with limiting the use of pipercillin-tazobactam and carbapenems while reducing use of other antibiotics as well. 10 Our findings suggest opportunities for further de-escalation that can occur based on quantitative assessments of antibiotic spectrum, especially for patients with bacteria-culture-negative HAP and VAP.…”
Section: Discussionmentioning
confidence: 75%
“…The decrease in utilisation of quinolones and anti-pseudomonal antibiotics occurred before the decrease in incidence density of C. difficile . In a local study, utilisation rate of broad-spectrum antibiotics had a significant negative correlation with incidence density of C. difficile and carbapenem-resistant P. aeruginosa but not with carbapenem-resistant A. baumannii [ 21 ]. The significant decreases in incidence density of MRSA and carbapenem-resistant and MDR A .…”
Section: Discussionmentioning
confidence: 99%